Adequacy of small biopsy and cytology specimens for comprehensive genomic profiling of patients with non-small-cell lung cancer to determine eligibility for immune checkpoint inhibitor and targeted therapy. Issue 9 (5th May 2021) - Faber, Erin; Grosu, Horiana; Sabir, Sharjeel; San Lucas, Francis Anthony; Barkoh, Bedia A; Bassett, Roland L; Luthra, Rajyalakshmi; Stewart, John; Roy-Chowdhuri, Sinchita
Abstract : Aims: In advanced-stage non-small-cell lung cancer (NSCLC), incomplete genotyping for guideline-recommended genomic biomarkers poses a significant challenge to making informed and timely clinical decisions. We report our institution's experience in assessing the adequacy of small specimens for comprehensive genomic profiling for guideline-recommended lung cancer biomarker testing. Methods: We performed a retrospective evaluation of all image-guided procedures for NSCLC performed in our institution between October 2016 and July 2018, including core needle biopsy (CNB) and fine-needle aspiration (FNA) in patients who had undergone genomic profiling for lung cancer. Lung cancer biomarker adequacy, defined as successful testing of guideline-recommended biomarkers including, epidermal growth factor receptor ( EGFR ); serine/threonine protein kinase B-Raf ( BRAF ); anaplastic lymphoma kinase ( ALK ); proto-oncogene tyrosine protein kinase ROS ( ROS1 ); Rearranged during Transfection ( RET ); Tyrosine protein kinase Met ( MET ); and programmed cell death ligand 1 (PD-L1), was evaluated. Results: A total of 865 cases were evaluated in this study, 785 of which included testing of all lung cancer biomarkers. Lung tissue was adequate for biomarker testing in 84% of cases; this rate increased to 87% when biomarker testing was combined with concurrently acquired FNA or CNB specimens. Biomarker testing success correlated strongly with DNA concentration (p<0.0001) and the use of 22G needles in endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) procedures (p=0.0035). Biomarker testing of CNB specimens showed a significantly higher success rate than did biomarker testing of cytology FNA specimens (p=0.0005). The adequacy of EBUS-TBNA samples was not significantly different from that of the transthoracic needle aspiration samples (p=0.40). Variables such as age, gender, lesion size, site, diagnosis and number of needle passes showed no significant correlation with success rates in lung cancer biomarker testing. Conclusion: The growing numbers of therapeutic biomarkers in NSCLC requires judicious triage of limited-volume tissue from small specimens. Our study showed that thoracic small tissue specimens can be used successfully to provide prognostic and predictive information for the current guideline-recommended biomarkers for NSCLC in most cases.